CONTRIBUTION OF SWALLOW’S NEST TAX AND LOCAL TAX TO LOCAL OWN REVENUE: EVIDENCE IN ONE OF THE REGION IN INDONESIA - Benny Prawiranegara; Dendy Syaiful Akbar; Wiwin Setianingsih; Anisa Lisara (Jurnal Wawasan dan Riset Akuntansi, 2020)
Swallow nest tax is a type of local tax. Meanwhile, local tax is one part or source of local own revenue. The existence of decentralization policy in Indonesia requires local governments to increase their financial independence. Increasing financial independence in an area is one of the successes of the decentralization policy. Ciamis is one of the regions in Indonesia, and the same as other regions are required to be able to optimize the sources of revenue, including those from local taxes. Ciamis has experienced a decline in independence because one of the tourist locations has been separated into a new autonomous region. Based on this, the purpose of this study is to analyze the contribution of swallow's nest tax to local tax and its contribution to local own revenue. This study uses a descriptive method with a quantitative approach. The method is used to explain phenomena and characteristics during research and to test and answer research questions. The results showed that swallow nest tax has a very low contribution to local taxes in the period 2013-2018. Whereas regional taxes in 2013-2015 had a very low contribution to local revenue, and in 2016-2018 had low criteria.